Translating for Children – World View or Pedagogics? - Stolze, Radegundis (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThis article discusses the translator’s approach to the task of translating. In an initial descriptive analysis of several German translations of an Italian novel a tendency towards linguistic simplification and over-explicitation in view of easy reading can be detected. Switching the perspective to the translator’s own dynamic view of text production, the necessary expert reading and hermeneutic understanding, as well as the coordination problem of various rhetoric criteria of writing are being discussed. Based on the translator’s social responsibility we may conclude that translators should be aware of the problems arising and reflect consciously on their formulation decisions regarding coherence, style and ideology.